PENGARUH GREEN ACCOUNTING DAN SUSTAINABILITY REPORT TERHADAP KINERJA KEUANGAN PERUSAHAAN (STUDI PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI) - Viona Adikasiwi; Widiatmoko, Jacobus; Indarti, MG Kentris (Pusat Penelitian dan Pengabdian bagi Masyarakat Politeknik Negeri Tanah Laut, 2024)
The research was conducted to test and analyze whether green accounting projected with index proper while sustainability reports projected by corporate social responsibility influenced the financial performance of companies with leverage and size of companies as controlling variables. The research objects used are manufacturing companies listed on the Indonesian Stock Exchange from 2018 to 2022. The sampling technique in this study uses purposive samplings with defined criteria, thus producing 249 data. The method used in this study is the double linear regression analysis method. The results of this research show that green accounting and sustainability reports have an impact on the financial performance of companies.